The Reservoir Age Effect Varies With the Mobilization of Pre-Aged Organic Carbon in a High-Altitude Central Asian Catchment - Schroeter, Natalie; Mingram, Jens; Kalanke, Julia; Lauterbach, Stefan; Tjallingii, Rik; Schwab, Valérie F.; Gleixner, Gerd (Frontiers in Earth Science, 2021)
Lake sediments provide excellent archives to study past environmental and hydrological changes at high temporal resolution. However, their utility is often restricted by chronological uncertainties due to the “reservoir age effect” (RAE), a phenomenon that results in anomalously old radiocarbon ages of total organic carbon (TOC) samples that is mainly attributed to the contribution of pre-aged carbon from aquatic organisms. Although the RAE is a well-known problem especially in high altitude lakes, detailed studies analyzing the temporal variations in the contribution of terrestrial and aquatic organic carbon (OC) on the RAE are scarce. This is partially due to the complexity of isolating individual compounds for subsequent compound-specific radiocarbon analysis (CSRA). We developed a rapid method for isolating individual short-chain (C16 and C18) and long-chain (>C24) saturated fatty acid methyl esters (FAMEs) by using high-pressure liquid chromatography (HPLC). Our method introduces only minor contaminations (0.50 ± 0.22 µg dead carbon on average) and requires only few injections (≤10), therefore offering clear advantages over traditional preparative gas chromatography (prep-GC). Here we show that radiocarbon values (Δ14C) of long-chain FAs, which originate from terrestrial higher plant waxes, reflect carbon from a substantially pre-aged OC reservoir, whereas the Δ14C of short-chain FAs that originate from aquatic sources were generally less pre-aged. 14C ages obtained from the long-chain FAs are in closer agreement with 14C ages of the corresponding bulk TOC fraction, indicating a high control of pre-aged terrestrial OC input from the catchment on TOC-derived 14C ages. Variations in the age offset between terrestrial and aquatic biomarkers are related to changes in bulk sediment log(Ti/K) that reflect variations in detrital input from the catchment. Our results indicate that the chronological offset between terrestrial and aquatic OC in this high-altitude catchment is mainly driven by temporal variations in the mobilization of pre-aged OC from the catchment. In conclusion, to obtain accurate and process-specific lake sediment chronologies, attention must be given to the temporal dynamics of the RAE. Variations in the apparent ages of aquatic and terrestrial contributions to the sediment and their mass balance can substantially alter the reservoir age effect.